GAMBARAN LAMA TIDUR TERHADAP PRESTASI BELAJAR SISWA - Marpaung, Panangian P.; Supit, Siantan; Nancy, Joice (Universitas Sam Ratulangi, 2013)
Abstract: Inadequate sleep leads to concentrating distraction, fatigue, mood and productivity disorder, etc. Therefore, these matters could contribute influence in teenagers, especially to their academic performance. Adequate sleeping length is needed by the body to maximize the student’s ability in effort of achieving a good academic performance. This descriptive study using cross sectional design. The samples were the students of SMA Binsus Manado. Samples consist of 116 students including male and female ranging in age from 15 to 18 years old. This study using a sleeping length questionnaire for figure out the distribution of the respondent’s sleeping length and to evaluate the student’s academic performance by using their mid-term exam results. The results of this study are presented in respondent distribution table. The highest number of 49,1% occupies a high academic performance with adequate sleep. The rest distributes as 22,4% in medium academic performance with adequate sleep, 6,0% in low academic performance with adequate sleep. 14,7% in high academic performance but with inadequate sleep, 6,9% in medium academic performance with inadequate sleep, and 0,9% with low academic performance and inadequate sleep. Generally, the students with adequate sleep result in high academic performance. Key words: description, sleeping length, studying performance, student. Abstrak: Kurang tidur cenderung menyebabkan gangguan konsentrasi, kelelahan, gangguan mood, produktivitas, dan lain-lain sehingga dapat mempengaruhi remaja terutama terhadap prestasi belajar. Lama tidur yang cukup dibutuhkan tubuh untuk memaksimalkan kemampuan siswa dalam usaha mencapai prestasi belajar yang baik. Penelitian ini merupakan penelitian deskriptif dengan desain penelitian cross sectional. Sampel merupakan siswa SMA Binsus Manado. Sampel berjumlah 116 orang laki–laki maupun perempuan dengan rentang usia 15–18 tahun. Untuk mengetahui distribusi lama tidur responden, digunakan kuesioner lama tidur sedangkan untuk menilai prestasi belajar digunakan nilai ujian mid semester. Hasil yang diperoleh disajikan dalam bentuk tabel distribusi responden dengan jumlah terbanyak sebesar 49,1% responden dengan prestasi tinggi dan cukup tidur Sisanya terdistribusi di 22,4% responden berprestasi sedang dan cukup tidur, 6,0% responden berprestasi rendah namun cukup tidur. Ada juga 14,7% responden berprestasi tinggi namun tidak cukup tidur, 6,9% responden berprestasi sedang namun tidak cukup tidur, serta 0,9% responden berprestasi rendah dan kurang tidur. Pada umumnya, siswa yang cukup tidur memiliki prestasi belajar yang tinggi. Kata Kunci: gambaran, lama tidur, prestasi belajar, siswa.